Dynamic Learning Networks Models and Cases in Action - Romano, Aldo; Secundo, Giustina (Springer US : Imprint: Springer, 2009)
Dynamic Learning Networks: Models and Cases In Action provides a network perspective of organizational learning to drive dynamic competition through extended firm learning processes. This edited volume contributed by worldwide experts in this field, provides academics and company managers with an extended view of organizational learning networks from real cases and different perspectives. The volume addresses Dynamic Learning Networks in two distinct ways: first, networks for managing change and learning; second, networks that learn. Main topics include: Knowledge Networks, High Performing Social Networks, Suppliers Networks, Solutions Networks, Corporate University 2.0 and Stakeholder University. Dynamic Learning Networks: Models and Cases In Action is designed for a professional audience, composed of researchers and practitioners working in corporate learning. This volume is also suitable for advanced-level students in computer science.